KOMPONEN HASIL BEBERAPA VARIETAS KEDELAI DI LAHAN PASANG SURUT TIPE C - Dwi Zulfita; Nurjani; Eddy Santoso (Program Studi Agroteknologi INSTIPER, 2019)
Utilization of tidal land as a medium for growing soybean plants is facing several obstacles such as high soil acidity and low soil fertility. Therefore, we need soybean varieties that are able to grow and produce well on the land—tolerant to other threatening factors. This study aims to find the best soybean variety on tidal land type C. The research method used is a Randomized Block Design (RCBD) with 6 The treatments are, A (Burangrang variety), B (Anjasmoro variety), C (Argomulyo variety), D (Dena variety 1), E (Gema variety) and F (Ring 1 variety). The treatments were repeated 4 times each, thus there were 24 experimental units in total. The results revealed that the Anjasmoro variety gives higher yields than the Burangrang, Argomulyo, Ring 1, Dena 1, and Gema varieties, and has the potential to grow well in type C tidal land. Keywords: Yield, Soybean, Tidal land, Varieties